Immune protection of chickens conferred by a vaccine consisting of attenuated strains of Salmonella Enteritidis, Typhimurium and Infantis - Varmuzova, Karolina; Faldynova, Marcela; Elsheimer-Matulova, Marta; Sebkova, Alena; Polansky, Ondrej; Havlickova, Hana; Sisak, Frantisek; Rychlik, Ivan (Veterinary research, 2016)
The colonization of poultry with different Salmonella enterica serovars poses an issue throughout the world. In this study we therefore tested the efficacy of a vaccine consisting of attenuated strains of Salmonella enterica serovars Enteritidis, Typhimurium and Infantis against challenge with the same serovars and with S. Agona, Dublin and Hadar. We tested oral and aerosol administration of the vaccine, with or without co-administration of cecal microbiota from adult hens. The protective effect was determined by bacterial counts of the challenge strains up to week 18 of life and by characterizing the immune response using real-time PCR specific for 16 different genes. We have shown that a vaccine consisting of attenuated S. Enteritidis, S. Typhimurium and S. Infantis protected chickens against challenge with the wild type strains of the same serovars and partially protected chickens also against challenge with isolates belonging to serovars Dublin or Hadar. Aerosol vaccination was more effective at inducing systemic immunity whilst oral vaccination stimulated a local immune response in the gut. Co-administration of cecal microbiota increased the protectiveness in the intestinal tract but slightly decreased the systemic immune response. Adjusting the vaccine composition and changing the administration route therefore affects vaccine efficacy.
Keywords: Vaccines, Attenuated; Salmonella enteritidis; nemoci drůbeže; Salmonella; mužské pohlaví; kombinované vakcíny; kur domácí; salmonelové vakcíny; Chickens; zvířata; Salmonella typhimurium; Poultry Diseases; Vaccines, Combined; Salmonella Vaccines; atenuované vakcíny; salmonelová infekce u zvířat; Salmonella Infections, Animal; Male; Animals